Language Rights of Newcomers and Indigenous Peoples in the African and European Contexts - Klinytskyi, Illia; Ugwu, Ikechukwu (Polish Review of International and European Law, 2025)
This article briefly discusses the problem of language coexistence in two legal contexts: Africa and Europe. The study reveals a pattern of agenda of modern regional legal practices: (a) the separation of people by preferred languages, and (b) the public policy of assimilation. Moreover, we pose our counterarguments to the ‘game-changing’ idea of the culture of justification in law: colonialism powered by the legal culture of duties continues its existence in internal and external affairs. Based on Tove Skutnabb-Kangas’s ‘linguicism’, the article queries the extent to which both the European Union and the African Union have gone to protect the linguistic rights of the Indigenous, tribal minorities and minoritised children, including refugee minorities.